A Crossroads in Genetic Counseling and Ethics - McGEE, Glenn (Cambridge quarterly of healthcare ethics, 1998)
Genetic counselors are on the front lines of the genetic revolution, presented with tests of varying predictive values and reliability, unfair testing distribution mechanisms, tests for conditions where no treatment exists, and companies that oversell the usefulness of their tests to physicians and nurses. Many scholars, both genetic testing task forces as well as the newly formed National Bioethics Advisory Commission, have all noted that genetic counseling programs and services are critical for adequate genetic testing. At the same time, in our own work at the University of Pennsylvania we have encountered many requests for new materials for training genetic counselors in ethics and providing ethics resources for genetic counseling. One of us has noted elsewhere that it is crucial that resources from the Human Genome Project, the Centers for Disease Control, and other public agencies be devoted to providing better resources for genetic counselors facing difficult ethical issues. Although the American Board of Genetic Counseling requires that training programs include some formal coursework in ethics, many wonder whether enough is being done to prepare genetic counselors for an ever-tougher job, and in particular there has been much concern expressed about whether “nondirectiveness” is an outmoded ideal that hampers this profession as it attempts to grow and identify the value of its practice. On the basis of many comments to us by genetic counselors and on the basis of our review of the current literature, we hypothesized that accredited genetic counseling training programs are poised at the turn of the century to begin planning a new approach to teaching the philosophy of genetic counseling, one that integrates philosophical, theoretical, and ethical training throughout the curriculum in genetic counseling.